2008
DOI: 10.1016/j.rmed.2008.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical features of Mycoplasma pneumoniae infection in children

Abstract: Mycoplasma pneumoniae (MP) is, considered to affect rarely children less than 5 yrs of age. This study was performed to describe the epidemiology and the clinical features of MP lower respiratory tract infection (LRTI) in children, presenting to a tertiary children hospital. Eleven month-longitudinal study of LRTI due to MP, diagnosed by polymerase chain reaction (PCR) on throat swab specimen, was performed. Out of 866 children with LRTI admitted to the Gaslini Pediatric Institute in Genoa, 102 had a positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

25
111
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(148 citation statements)
references
References 18 publications
(31 reference statements)
25
111
2
4
Order By: Relevance
“…In agreement with the current study results, other studies reported that children aged above 5 years had the higher rates of M. pneumoniae infections in comparison with children less than 5 years old (15)(16)(17). In the current study, the detection of M. pneumoniae DNA in the nasopharynx swabs was performed by the amplification of the P1 gene and 11 out of 136 cases (8.08%) were positive.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with the current study results, other studies reported that children aged above 5 years had the higher rates of M. pneumoniae infections in comparison with children less than 5 years old (15)(16)(17). In the current study, the detection of M. pneumoniae DNA in the nasopharynx swabs was performed by the amplification of the P1 gene and 11 out of 136 cases (8.08%) were positive.…”
Section: Discussionsupporting
confidence: 91%
“…As already mentioned earlier, the severity of disease and disease presentation in affected children younger than five years old tend to be less severe and different than those older, according to the clinical observations done during this study as well as according to some others [4,5,10] . Patients with higher titers of antibodies took longer time to recover from fever, cough and abnormal lungs findings.…”
Section: Discussionsupporting
confidence: 69%
“…Recent studies have concluded that children under five years, including infants, are more commonly affected by Mycoplasma pneumoniae [1][2][3][4][5][6][7] . From the data collected in our ward itself, out of the 504 cases admitted from January 2010 to December 2010, 33.7% were younger than five years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 M. pneumoniae is a common cause of CAP and other community-acquired lower respiratory tract infections (CA-LRTIs), particularly in school-age children and adolescents, but there are large gaps in our understanding of this disease. 3,4 Prevalence estimates vary from 10% to 40% in pediatric CA-LRTI, [5][6][7][8][9] and few studies address treatment recommendations. 4,10 Additionally, the IDSA guidelines target the use of macrolides in CA-LRTI as an area needing additional research.…”
mentioning
confidence: 99%